Knowledge-map analysis of bladder cancer immunotherapy - Zongwei Lv; Junhui Hou; Yuan Wang; Xia Wang; Yibing Wang; Kefeng Wang (Human Vaccines & Immunotherapeutics)
This study aimed to conduct a bibliometric analysis in the field of bladder cancer (BC) immunotherapy, and explore the research trends, hotspots and frontiers from 2000 to 2022. VOSviewer software was used to analyze the collaborative relationships between authors, institutions, countries/regions, and journals through citation, co-authorship, and co-citation analysis, to identify research hotspots and frontiers in this field. Researchers based in the United States of America have published a total of 627 papers with 27,308 citations. Indeed, the USA ranked first among the top 10 most active countries and showed the most extensive collaboration with other countries. The University of Texas MD Anderson CANC CTR has published 58 articles, making it the top most institution in terms of published articles and active collaborative research. Kamat AM and Lamm DL were the most active and co-cited authors with 28 papers and 980 co-citations, respectively. Chang Yuan and Xu le were the most active collaborative authors with a total link strength of 195. The J UROLOGY was the most active and frequently co-cited journal, with 100 papers and 6,668 co-citations. Studies of BC immunotherapy can be broadly classified into three categories: “basic research”, “clinical trial”, and “prognosis”. Our findings provide an overview of the research priorities and future directions of BC immunotherapy. Tumor microenvironment and immune checkpoint inhibitors (ICIs) of BC, as well as the combination of ICIs with other drugs, may become the main direction of future research.